The association between body mass index (bmi) status and dietary intake pattern with menstrual irregularities of undergraduate students in school of Health Sciences, Universiti Sains Malaysia (USM) - Susaidin, Noraishah (Universiti Sains Malaysia, 2024)
This study aimed to identify the association between body mass index (BMI) status and dietary intake patterns with irregular menstrual cycle among undergraduate students in School of Health Sciences, USM. A total of 179 undergraduate students aged between 19 and 25 years from all programs available in Health Campus were involved in this study. The study was conducted using a cross-sectional design and used convenience random sampling method. The data for this study was obtained through a set of online questionnaires to collect socio-demographic, anthropometric, dietary intake patterns and menstrual cycle information. The weight and height of each participant in this study were measured using a scale and stadiometer before they started to answer a set of questionnaires. The dietary information of the subjects was collected using the Food Frequency Questionnaire (FFQ) which adapted from five previous studies. The results of the study showed that 62% of the subjects with majority were 22 years old recorded having irregular menstrual cycles and the remaining 38% recorded having regular menstrual cycles. The study found that students with irregular menstrual cycles frequently consumed alcoholic beverages (n=1), caffeinated beverages (60.6%) and snacks (59.4%). In addition, students with these problems also ate less vegetables (62%), fruits (60.7%) and dairy products (61.8%). In addition, the study also did not find a significant association between weight status and dietary intake patterns with irregular menstrual cycle problems among undergraduate students in School of Health Science, Universiti Sains Malaysia. Therefore, further studies are needed to get a clearer picture of the link between body mass index (BMI) status and dietary intake patterns with irregular menstrual cycle problems.